Monetary Policy and Its Unintended Consequences - Levin, Andrew T. (Journal of Economic Literature, 2024)
Andrew T. Levin of Dartmouth College and NBER reviews “Monetary Policy and Its Unintended Consequences” by Raghuram Rajan. The EconLit abstract of this book begins: “Details how monetary adventurism can have unintended effects and promotes policy that is moderate and focused on combating high inflation and financial instability.”